Perencanaan Drainase di Jalan Goropaa RT 01/RW 01 Kelurahan Bugis Kota Gorontalo - Muhammad Ikhsan; Mohammad Imran (Journal of Applied Geoscience and Engineering, 2025)
This study aims to formulate a practical drainage plan for Goropaa Street RT 01/RW 01, Bugis Village, Gorontalo City, based on field conditions and local construction costs. The study used a quantitative descriptive approach through site surveys, visual documentation, and direct measurement of the planned channel alignment. The technical design adopted the existing channel dimensions on the opposite side of the road to maintain flow continuity and simplify construction. Work volumes were calculated using basic geometric formulas for excavation, sand bedding, stone masonry, and plastering. Cost estimation was prepared using the work coefficients in the Circular Letter of the Directorate General of Construction Development Number 68/SE/Dk/2024 and local unit prices for materials and labor. The results show that the planned drainage channel length of 60.8 m requires an estimated budget of IDR 20.875.831,17. The plan is considered applicable because it uses dimensions that fit the site, relies on locally available materials, and can be implemented with relatively simple construction methods.